Obiekty kosztowe w tradycyjnym rachunku kosztów i w rachunku kosztów działań - Putyra, Adam (Cost Objects in Traditional Costing System and in Activity Based Costing, 2009)
Activity based costing (ABC) puts an accent on the cause and effect relation at each stage of allocating costs. That is why this system identifies a lot of costs objects which are responsible for incurring costs. In contrast to traditional costing system ABC defining many costs objects ensures much more reliable cost information. It is partly achieved thanks to wider scope of direct costs implied by wider catalogue of costs objects. The paper presents the differences in cost objects structure between traditional costing system and activity based costing. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 109-118